Economic Policy Uncertainty, Trust and Inflation Expectations - Klodiana Istrefi; Anamaria Piloiu (Center for Economic Studies and ifo Institute (CESifo), 2013)
Theory and evidence suggest that in an environment of well-anchored expectations, temporary news or shocks to economic variables, should not affect agents' expectations of inflation in the long term. Our estimated structural VARs show that both long- and short-term inflation expectations are sensible to policy-related uncertainty shocks. A rise of long-term inflation expectations in times of economic contraction, in response to such shocks, suggests that heightened policy uncertainty observed during the recent years indeed raises concerns about future inflation. Furthermore, both monetary and fiscal policy-related uncertainties are significant for the negative dynamics in citizens' trust in the ECB.
Keywords: E02; E31; E58; E63; P16; 330; policy uncertainty; central banks; inflation expectations; structural VAR